Hubungan Polimorfisme Gen Interleukin 10 - 819 C/T Pada Kejadian Preeklampsia Ibu Hamil di Puskesmas Dalu X B Tanjung Morawa Deli Serdang - Liza Mutia; Karolina br. Surbakti; Selamat Riadi (Jurnal Ners, 2023)
Preeclampsia is one of the disorders during pregnancy, characterized by increased blood pressure and proteinuria, causing an increase in morbidity and mortality in the mother and fetus. Interleukin 10 (IL10) is called a T helper type 2 (Th2) cytokine which is important because it acts as an anti-inflammatory which functions for the maintenance and development of pregnancy and forms immunity to inhibit the secretion of T helper 1 (Th1) cytokines such as IL 6, TNF alpha and INF Gamma. Genotypic variation can provide information about individual differences in the secretion of IL-10 and the tendency to the incidence of preeclampsia. The IL 10 - 819 C/T gene polymorphism is located on chromosome 1q32.2 distal to the promoter area and is a transcription factor of the IL 10 gene. The aim of this study was to determine the relationship between 10-819 C/T Interleukin Gene Polymorphisms in the incidence of preeclampsia in pregnant women. The method used to determine the IL 10 819 C/T polymorphism with RFLP PCR. Results. The distribution of IL 10-819 C/T genotypes in the control group had 5 people (23.73%) of TT genetic variation, 15 people with CT (65.21%) and 3 people with CC genetic variation (13.04%). ). In the Preeclampsia group, there were 7 people (30.43%) with genetic variation of TT and there were 10 people (43.47%) with genetic variation of CT as many as 6 people (26.08%) with CC variation. There was no correlation between interleukin gene polymorphism 10-891 C/T with the incidence of preeclampsia in pregnant women at Dalu X B Health Center Tanjung Morawa, Deli Serdang